2007
DOI: 10.3177/jnsv.53.315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Kinds of Edible Seaweeds in Diets on the Development of D-Galactosamine-Induced Hepatopathy in Rats

Abstract: SummaryIn the present study we investigated the effects of 11 kinds of edible seaweeds (6 brown and 5 red algae) which contain characteristic seaweed dietary fibers on the induction of D -GalN ( D -galactosamine)-hepatopathy in rats (Exps. 1 and 2). Then, the efficacy of various components prepared from Gelidium sp., which was found to alleviate the hepatopathy in Exps. 1 and 2, was examined (Exp. 3). The rats were fed the diets containing various kinds of seaweeds (Exps. 1 and 2), or several components of Gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Fucoidan prevented concanavalin A-induced liver injury by mediating the endogenous interleukin (IL)-10 production and the inhibition of proinflammatory cytokine in mice [ 118 ]. The dietary fiber in edible brown seaweeds ( Laminaria sp ., Sargassum fulvellum and Eisenia bicyclis ) had the repressive effect against D-galactosamine (D-GalN)-induced hepatopathy and the protective effect was caused at least in part by fucoidan [ 119 , 120 ]. Hepatic fibrosis results from chronic damage to the liver in conjunction with the progressive accumulation of fibrillar extracellular matrix proteins.…”
Section: Bioactivitymentioning
confidence: 99%
“…Fucoidan prevented concanavalin A-induced liver injury by mediating the endogenous interleukin (IL)-10 production and the inhibition of proinflammatory cytokine in mice [ 118 ]. The dietary fiber in edible brown seaweeds ( Laminaria sp ., Sargassum fulvellum and Eisenia bicyclis ) had the repressive effect against D-galactosamine (D-GalN)-induced hepatopathy and the protective effect was caused at least in part by fucoidan [ 119 , 120 ]. Hepatic fibrosis results from chronic damage to the liver in conjunction with the progressive accumulation of fibrillar extracellular matrix proteins.…”
Section: Bioactivitymentioning
confidence: 99%
“…Kawano had previously identified therapeutic potential of edible whole seaweeds in the diet of experimental rats with this type of liver damage [75]. In his 2007 study he identified the components of the seaweeds that gave rise to the inhibition of liver disease.…”
Section: Therapies From Fucoidanmentioning
confidence: 99%
“…In his 2007 study he identified the components of the seaweeds that gave rise to the inhibition of liver disease. The elevated levels of aspartate and alanine aminotransferases were inhibited specifically by the fucoidan in the diet at levels equivalent to those in whole seaweed at 5% of the total diet [75,76]. Lastly, Hayakawa addressed the issue of hepatocarcinoma in ex vivo samples of chronic cirrhosis and hepatitis B and C from a clinical setting and found that Fucus vesiculosis fucoidan has a potentially therapeutic effect [77].…”
Section: Therapies From Fucoidanmentioning
confidence: 99%
“…In particular, Granert and colleagues in 1999 demonstrated that fucoidan inhibited inflammatory infiltration [ 21 ], and in 2012 Kang and Cui showed the protective effect of fucoidan on lipopolysaccharide (LPS)-induced rat neuronal damage [ 22 23 ]. In addition, with regard to liver damage, ConA and D-galactosamine (GalN)-induced hepatopathy was improved, as indicated by Kawanno and Saito [ 24 25 ]. Common findings in these studies were the downregulation of related pro-inflammatory factors, including TNF-α, IFN-γ, IL-6, IL-8 and IL-12, and established the foundation of anti-inflammatory treatment.…”
Section: Introductionmentioning
confidence: 99%